The Role of GPNMB in Inflammation - Saade, Marina; Araujo de Souza, Giovanna; Scavone, Cristoforo; Kinoshita, Paula Fernanda (Frontiers in Immunology, 2021)
Inflammation is a response to a lesion in the tissue or infection. This process occurs in a specific manner in the central nervous system and is called neuroinflammation, which is involved in neurodegenerative diseases. GPNMB, an endogenous glycoprotein, has been recently related to inflammation and neuroinflammation. GPNMB is highly expressed in macrophages and microglia, which are cells involved with rapid inflammation response in the periphery and the brain, respectively. Some studies have shown increased levels of GPNMB in pro-inflammatory conditions, such as LPS treatment, and in pathological conditions, such as neurodegenerative diseases and cancer. However, the role of GPNMB in inflammation is still not clear. Even though most studies suggest that GPNMB might have an antiinflammatory role by promoting inflammation resolution, there is evidence that GPNMB could be pro-inflammatory. In this review, we gather and discuss the published evidence regarding this interaction.